Political Polarization and Internal Conflict: A Cross-National Analysis Using Popular Support and Government Cohesion as Proxies - Parsons, Brandon (International Journal of Economics and Financial Issues, 2024)
The study uses proxies of political polarization, popular support of the government, and government cohesion, to examine its role in explaining internal conflict and the specific types of political violence and civil disorder. The study uses panel data from 135 countries from 1990 to 2021. The research uses two econometric models, Quantile via Moments, to examine the effects of popular support and government cohesion across the distribution of internal conflict, and two-way fixed effects with Driscoll and Kraay standard errors. The two models account for heteroscedasticity, cross-sectional dependence, and autocorrelation. The study finds popular support of the government and its cohesion robustly explain internal conflict and its specific forms of political violence and civil disorder. The research also finds political polarization that reduces popular support and government cohesion influences internal conflict regardless of regime type. The variables are significant from autocratic to democratic, suggesting political polarization that reduces popular support and government cohesion can negatively affect internal conflict levels irrespective of regime. Finally, the study finds the internet has a minor mitigating impact on internal conflict, while its interaction with popular support and government cohesion slightly exacerbates internal conflict.